2022
DOI: 10.1039/d1cp05348e
|View full text |Cite
|
Sign up to set email alerts
|

Giant dielectric response and relaxation behavior in (Tm + Ta) co-doped TiO2 ceramics

Abstract: Dielectric materials with huge dielectric constants are attracting attention due to the growing demand for microelectronics and high energy-storage devices. In this work, Tm + Ta co-doped TiO2 ceramics were...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…A second circular arc and non-zero intercept with the real Z axis is observed in the high frequency region for the samples with x = 0 and x > 0, respectively. This behavior is similar to what is reported for CaCu 3 Ti 4 O 12 [32] and co-doped TiO 2 [2,13]. The arc at high frequency (/non zero intercept) is attributed to the response of the semiconductor component (grains), while the larger arc represents the response of electrically insulating component (grain-boundaries).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…A second circular arc and non-zero intercept with the real Z axis is observed in the high frequency region for the samples with x = 0 and x > 0, respectively. This behavior is similar to what is reported for CaCu 3 Ti 4 O 12 [32] and co-doped TiO 2 [2,13]. The arc at high frequency (/non zero intercept) is attributed to the response of the semiconductor component (grains), while the larger arc represents the response of electrically insulating component (grain-boundaries).…”
Section: Resultssupporting
confidence: 86%
“…The room temperature relative permittivity (ε ) of pure TiO 2 is ~100, which is not suitable for practical energy storage applications. Interestingly, recent studies reported colossal relative permittivity (CP) for co-doped TiO 2 in the form (A, B) x Ti 1−x O 2 , where A is pentavalent and B is tri-or bivalent cations [2][3][4][5][6]. The origin of CP of the co-doped TiO 2 ceramics is controversially discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For heterogeneous ceramics, double (back-to-back) Schottky barriers are formed at the interfaces between n-type grains, leading to a bending of the conducting band at the grain boundaries, which results in a Φ b . 5,24 Under DC bias, the potential becomes unbalanced, resulting in an increase in reverse Φ b and a decrease in forward Φ b , as shown in Figure 9D. This may result in a large amount of space charge across the grain boundary barrier, resulting in an increase in ε r and tan δ.…”
Section: Resultsmentioning
confidence: 99%
“…Materials with large dielectric constants ( ε r > 10 3 ) are receiving increasing focus, due to their use in manufacturing capacitors, thermoelectric, and photoelectric sensors 1–3 . However, the high tan δ and sensitivity temperature/frequency stability of CP materials limit their widespread use in industry, and there is controversy over the origin and mechanism of CP 4–6 . Therefore, CP materials have been a hot topic of focus for researchers.…”
Section: Introductionmentioning
confidence: 99%